Exploring the process to obtain a composite based on Cr2O3–AlN using a method of hot pressing - Prokopiv, Nikolay; Kharchenko, Oleg; Gevorkyan, Edwin; Gutsalenko, Yuriy (Eastern-European Journal of Enterprise Technologies, 2019)
We have established the influence of heating rate of 150, 350 and 600 °C/min, pressure of 8 and 18 MPa, on the compaction process of the reaction mixture Cr2O3–15AlNnano, the hardness and crack resistance of the dense material. The intensity of compacting the charge Cr2O3–15AlNnano depends on the pressure magnitude and the rate of heating. A pressure of 18 MPa ensures the complete compaction of the mixture regardless of the specified heating rate while a pressure of 8 MPa provides for the complete compaction of the material only at the rate of heating of 600 °C/min. For the heating rate of 600 °C/min, compaction curves of the mixture at pressures 8 and 18 MPa are similar in shape. It was established that at a heating rate of 600 °C/min the compaction process of the mixture, in addition to pressure, is additionally activated by the effect of exothermic reaction among its components. Increasing the rate of heating from 150 to 600 °C makes it possible to improve the hardness and crack resistance of the dense material by, respectively, 1.0 GPa and 1.5MPa∙m1/2. It was revealed that the structure of the dense material, newly formed during HP(Hot pressing) of the mixture Cr2O3–15AlNnano, is of the dispersed-strengthened type: the matrix phase from a solid solution of variable composition from the composition (Cr1-x–Alx)2О3 (0<x<0.4) and the dispersed, stochastically distributed within it, Cr2N inclusions the size of up to 2 µm that are alloyed with Al to 1.8 %. We have identified separate large inclusions the size of 10–40 μm of the structure, similar to the basic structure, but with the matrix phase of solid solution of the composition (Cr1-x–Alx)2О3 (0.5<x<0.9). The fracture toughness of the material, obtained in the course of research, is 1.5 times larger, while the hardness is 1.2 GPa less, than similar characteristics for the most common ceramics of the "mixed" type based on Al2O3–ТіС.